STUDENTS’ QUESTIONS IN INQUIRY-BASED CHEMISTRY CLASSROOMS - Winnie Sim Siew Li; Mohamad Yusof Arshad (Program Pascasarjana Universitas Negeri Jakarta, 2016)
Questioning plays an important part in the teaching and learning science. Previous research has extensively focused on teachers‟ questions compared to students‟ questions. Research of students‟ questions is vital as it shows how students think and their understanding of a content studied. Hence, this research focuses on students‟ questions, types of questions asked and the sequence(s) after students‟ question. Twenty three chemistry teachers and their students of national secondary schools were involved in this study. Ninety two chemistry lessons were observed, audio and video recorded. Transcript of the lessons showed that students‟ questions were mainly related to content or science process skills as emphasised in inquiry teaching and learning. However, most questions asked by students were low order closed questions. The sequence after students‟ questions with the highest percentage (83.33%) was IR (Initiation from student, followed by teachers‟ response). This sequence showed that chemistry teachers in this study did not display inquiry-based questioning characteristics because in inquiry teaching, teachers should avoid responding to students‟ questions. Instead, they should provide opportunities for students to respond to their friends‟ questions. Hence, teachers should move towards student initiated inquiry, where students ask higher order thinking questions and increasing the interaction among the students.